Laser tube technology ‐ A new automation procedure in end‐preparation of CHS‐to‐CHS intersections welded by partial joint penetration (PJP): design, constructional and experimental remarks. Issue 2 (1st September 2021) - Mastropasqua, Augusto; Majowiecki, Massimo; Duarte, Claudio
Abstract: Over the past decade, the manufacturers of the most advanced laser‐cutting machinery have made significant breakthroughs in the CNC (computer numerical control) field, by utilizing the efficiency of the reversible laser‐beam (multi‐axis robotic system). In this paper, welded tubular connections for structural applications are studied with explicit reference to these new end‐machining possibilities. In particular, the case of circular hollow sections (CHS) is dealt with, whereby the class of connection typically referred to is known as CHS‐to‐CHS connections. Thanks to the Laser‐Tube‐Cutting technology (LTC), it is now possible, for Partial Joint Penetration (PJP) or Compound Joint Penetration (FW+PJP) to establish size, position and spatial inclination of the throat‐plane along the welded path, allowing the structural designers to better simulate the real stress distribution through the welded region (WR) and the nominal throat‐plane (TP) surface. The study is concluded with some interesting as‐built case studies and the results obtained from an LTC‐experimental phase aimed at obtaining 5 samples that are wholly compatible to the EN(ISO)9692, AS/NZS1554 and AWS‐D1.1 welding codes.